2016
DOI: 10.1371/journal.pone.0164002
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Agriculture Platforms for Nutrition: A Case Study of a Participatory, Video-Based Agricultural Extension Platform in India

Abstract: Successful integration of nutrition interventions into large-scale development programmes from nutrition-relevant sectors, such as agriculture, can address critical underlying determinants of undernutrition and enhance the coverage and effectiveness of on-going nutrition-specific activities. However, evidence on how this can be done is limited. This study examines the feasibility of delivering maternal, infant, and young child nutrition behaviour change communication through an innovative agricultural extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
(37 reference statements)
1
32
0
1
Order By: Relevance
“…Twenty‐two interventions occurred in sub‐Saharan Africa (Aidam et al, n.d.; Aubel, Touré, & Diagne, ; Alive and Thrive Ethiopia, ; Berti, Mildon, Siekmans, Main, & Macdonald, ; Bruyeron, Denizeau, Berger, & Trèche, ; Chiutsi‐Phiri et al, ; Crossman et al, ; Fernald et al, ; Gelli et al, ; Gelli et al, ; Guyon et al, ; Harris et al, ; Kim et al, ; Kimani‐Murage et al, ; Kulwa et al, ; Leroy, Olney, & Ruel, ; Mukuria, Martin, Egondi, Bingham, & Thuita, ; Mulualem, Henry, Berhanu, & Whiting, ; Nikiema et al, ; Olney, Pedehombga, Ruel, & Dillon, ; Parvanta, Thomas, & Zaman, ; Sarrassat et al, ; Save the Children, ; Webb Girard et al, ; Alive and Thrive, 2016) and 11 in Bangladesh (Aboud & Akhter, ; Aboud, Moore, & Akhter, ; Aboud, Shafique, & Akhter, ; Frongillo et al, ; Hoddinott, Ahmed, Ahmed, & Roy, ; Kimmons et al, ; Owais et al, ; Parvanta et al, ; Roy et al, ; Roy et al, ; TANGO International, ). Of the remaining, nine occurred in India (Alive & Thrive India, n.d.; Bhandari et al, ; Bhandari et al, ; Dongre, Deshmukh, & Garg, ; Kadiyala, Morgan, Cyriac, Margolies, & Roopnaraine, ; Kilaru, Griffiths, Ganapathy, & Ghosh, ; Palwala et al, ; Singh et al, ; Vazir et al, ) and eight Central/South American or Mexico (Bonvecchio, Pelto, Escalante, & Monterrubio, ; de Oliveira, Giugliani, Santo, & Nunes, ; Iannotti et al, ; Jensen, Frongillo, Leroy, & Blake, ; Leroy et al, ; Monterrosa et al, ; Penny et al, ; Santos et al, ). Five were implemented in China (Guldan et al, ; Li et al, ; Sun et al, ; J. Zhang, Shi, Chen, Wang, & Wang,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐two interventions occurred in sub‐Saharan Africa (Aidam et al, n.d.; Aubel, Touré, & Diagne, ; Alive and Thrive Ethiopia, ; Berti, Mildon, Siekmans, Main, & Macdonald, ; Bruyeron, Denizeau, Berger, & Trèche, ; Chiutsi‐Phiri et al, ; Crossman et al, ; Fernald et al, ; Gelli et al, ; Gelli et al, ; Guyon et al, ; Harris et al, ; Kim et al, ; Kimani‐Murage et al, ; Kulwa et al, ; Leroy, Olney, & Ruel, ; Mukuria, Martin, Egondi, Bingham, & Thuita, ; Mulualem, Henry, Berhanu, & Whiting, ; Nikiema et al, ; Olney, Pedehombga, Ruel, & Dillon, ; Parvanta, Thomas, & Zaman, ; Sarrassat et al, ; Save the Children, ; Webb Girard et al, ; Alive and Thrive, 2016) and 11 in Bangladesh (Aboud & Akhter, ; Aboud, Moore, & Akhter, ; Aboud, Shafique, & Akhter, ; Frongillo et al, ; Hoddinott, Ahmed, Ahmed, & Roy, ; Kimmons et al, ; Owais et al, ; Parvanta et al, ; Roy et al, ; Roy et al, ; TANGO International, ). Of the remaining, nine occurred in India (Alive & Thrive India, n.d.; Bhandari et al, ; Bhandari et al, ; Dongre, Deshmukh, & Garg, ; Kadiyala, Morgan, Cyriac, Margolies, & Roopnaraine, ; Kilaru, Griffiths, Ganapathy, & Ghosh, ; Palwala et al, ; Singh et al, ; Vazir et al, ) and eight Central/South American or Mexico (Bonvecchio, Pelto, Escalante, & Monterrubio, ; de Oliveira, Giugliani, Santo, & Nunes, ; Iannotti et al, ; Jensen, Frongillo, Leroy, & Blake, ; Leroy et al, ; Monterrosa et al, ; Penny et al, ; Santos et al, ). Five were implemented in China (Guldan et al, ; Li et al, ; Sun et al, ; J. Zhang, Shi, Chen, Wang, & Wang,…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to assess whether patterns emerged between the type and/or quantity of BCT used and intervention effectiveness. Of the 64 unique interventions identified, six (Alive & Thrive India, n.d.; Fernald et al, ; Gelli, Becquey, et al, ; Gelli, Margolies, et al, ; Kadiyala et al, ; Kulwa et al, ) were in progress and had not reported evaluation data as of August 2018. Forty‐two were randomized controlled or quasi‐experimental studies, and one was a propensity score matched impact evaluation; the remaining interventions applied evaluation strategies that consisted of pre/post designs with no control group ( n = 15), cross‐sectional surveys ( n = 1), or were missing baseline data ( n = 1) and were excluded from these analyses.…”
Section: Resultsmentioning
confidence: 99%
“…A further conceptual point for discussion regarding differences between intersectoral and multisectoral interventions for stunting arises from the analysis of factors that condition ISA. Nutrition-speci c interventions rely on the health sector (7) but there is ample recognition that many additional sectors have roles to play in nutrition-sensitive interventions (11,(30)(31)(32). During planning and implementation of the intervention against stunting in Bogotá, a lack of engagement of the health sector was frequently seen as a barrier for ISA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is found in the literature of the different pathways linking agriculture and nutrition (World Bank 2007;FAO 2013;Kadiyala et al 2014;Kadiyala et al 2016;Gillespie and van den Bold 2017). Taking into account the spatial influence of farming practices, cultural settings, resource availability at a household level, and soil and agro-ecological environment, what may be considered a fitting strategy at one place, while providing the framework, is unlikely to be directly applicable in a different setting.…”
Section: Introductionmentioning
confidence: 99%